УПОРЯДОЧЕННЫЕ ВЫБОРКИ В ПРЕОБРАЗОВАНИЯХ ПОСЛЕДОВАТЕЛЬНОСТЕЙ НЕКОРЕЛЛИРОВАННЫХ ДАННЫХ - Мазманян, Р.О. (Інститут електродинаміки НАН України, Київ, 2018)
The coherence function for an arbitrary pair the input sequence – a given element of ordered samples random data’s is defined. The essentially nonlinear character of this data processing method is established. Parametric and statistical estimates of the proximity of median transformations to the normal Gaussian distribution law are obtained. A technique for applying the Pearson criterion for estimating the statistical proximity of analytically defined functions is presented. References 15, figures 7.